Exploring the effect of chain length of bridging ligands in cobalt(II) coordination polymers based on flexible bis(5,6-dimethylbenzimidazole) ligands: Synthesis, crystal structures, fluorescence and catalytic properties - Qin, Li; Li, Yue-Hua; Ma, Pei-Juan; Cui, Guang-Hua (Journal of molecular structure, 2013)
Two new Co(II) metal–organic coordination polymers have been hydrothermally synthesized using flexible bis(5,6-dimethylbenzimidazole) ligands with varying chain lengths with 5-nitroisophthalic auxiliary ligand. 1 features a 1D looped-like chain consisting of two kinds of macrocycles alternately, and 2 possesses a 4-connected twofold interpenetrating diamond network structure. Moreover, the two compounds as a heterogeneous catalysts present high efficiency for the degradation of methyl orange dye in Fenton-like process. [Display omitted] •Two CoII coordination polymers have been characterized.•The influences of chain lengths on framework were discussed.•TG analysis confirms the stability of the coordination polymers.•Luminescence properties of complexes have been investigated.•Complexes show higher activity for degradation of methyl orange. Two Co(II) coordination polymers derived from a dicarboxylate and two flexible bis(5,6-dimethylbenzimidazole) ligands with varying chain lengths equipped, namely [Co(bdmbmm)(nip)]n (1) and [Co2(bdmbmb)2(nip)2⋅H2O]n (2) (bdmbmm=1,1′-bis(5,6-dimethylbenzimidazole)methane, H2nip=5-nitroisophthalic acid, bdmbmb=1,4-bis(5,6-dimethylbenzimidazole)butane), have been synthesized by hydrothermal methods and characterized by elemental analyses, IR spectra, thermogravimetric analysis (TGA), X-ray powder diffraction (XRPD) and single-crystal X-ray diffraction. Complex 1 forms a 1D looped-like chain consisting of two kinds of macrocycles, which is further arranged into a 2D supramolecular layer through face-to-face π–π stacking interactions; whereas complex 2 exhibits a 3D framework with a twofold interpenetrating diamondoid topology. The fluorescence and catalytic properties of the complexes for the degradation of methyl orange by sodium persulfate have been investigated.